2016
DOI: 10.1007/s12020-016-1106-3
|View full text |Cite|
|
Sign up to set email alerts
|

Chronic hyperglycemia affects bone metabolism in adult zebrafish scale model

Abstract: Type II diabetes mellitus is a metabolic disease characterized by chronic hyperglycemia that induce other pathologies including diabetic retinopathy and bone disease. The mechanisms implicated in bone alterations induced by type II diabetes mellitus have been debated for years and are not yet clear because there are other factors involved that hide bone mineral density alterations. Despite this, it is well known that chronic hyperglycemia affects bone health causing fragility, mechanical strength reduction and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 29 publications
2
40
0
1
Order By: Relevance
“…Moreover, they found that the transgenic homologous zebrafish has a reduction in scale size. This has been reported in other zebrafish type 1 diabetes models as well (Carnovali et al, ; Riddle et al, ). Neither of these studies have specifically looked into the rest of the skeletal structures.…”
Section: A Mexicanus As a Model To Identify Adult Skeletal Disorderssupporting
confidence: 75%
“…Moreover, they found that the transgenic homologous zebrafish has a reduction in scale size. This has been reported in other zebrafish type 1 diabetes models as well (Carnovali et al, ; Riddle et al, ). Neither of these studies have specifically looked into the rest of the skeletal structures.…”
Section: A Mexicanus As a Model To Identify Adult Skeletal Disorderssupporting
confidence: 75%
“…The zebrafish scale is a thin membranous bone embedded in the skin that consists of OBs, OCs, and bone matrix. Although the structure of zebrafish scales is rather simple compared with mammalian bones [3][4][5] , various in vivo and in vitro studies have demonstrated that OCs and OBs in teleost scales respond to hormones and other substances as one would predict from observation of the mammalian bone [6][7][8][9][10][11][12] , indicating that fundamental cellular and molecular programs that regulate OCs and OBs are highly conserved amongst vertebrates. In addition, this "surface" bone tissue enables in vivo live-imaging of OCs and OBs using fluorescent transgenic lines.…”
mentioning
confidence: 99%
“…In the study by Carnovali et al [18], the authors introduced a new model for studying glucose and bone metabolism. Using the scales of zebrafish, a suitable model, Carnovali et al [18] examined the effect of hyperglycemia on bone metabolism.…”
mentioning
confidence: 99%